Estudo numérico do desempenho de uma bomba centrífuga de múltiplos estágios operando com CO2 supercrítico - Fava, Felipe Coelho de Andrade (2021)
The present study aims to carry out the numerical study of the flow in a multistage centrifugal pump operating with CO2 under supercritical conditions. A numerical methodology is developed in the ANSYS CFX ® computational fluid dynamics program to simulate the flow inside the multistage pump. The thermophysical properties are obtained through a thermodynamic table (RGP), with data extracted from the NIST®-REFPROP program. The collected data will be used to survey the pump performance curves, as well as to analyze the flow fields and temperature gain across the pump stages. The results contribute to the analysis of the feasibility of using multistage centrifugal pumps for pumping supercritical CO2 in the pressure range from 75 to 95 bar, with temperatures between 35oC and 45oC and flow rates ranging between 30% and 150% of the best efficiency point indicated in the catalogue, thus being a topic of interest in deepwater oil production.